2013
DOI: 10.1155/2013/109219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bronchiectasis in Asthma according to Oral Steroid Requirement: Influence of Immunoglobulin Levels

Abstract: Purpose. To establish the prevalence of bronchiectasis in asthma in relation to patients' oral corticosteroid requirements and to explore whether the increased risk is due to blood immunoglobulin (Ig) concentration. Methods. Case-control cross-sectional study, including 100 sex- and age-matched patients, 50 with non-steroid-dependent asthma (NSDA) and 50 with steroid-dependent asthma (SDA). Study protocol: (a) measurement of Ig and gG subclass concentration; (b) forced spirometry; and (c) high-resolution thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Structural changes are common in HRCT of patients with asthma, especially for those with more severe disease, as bronchial wall thickness and air trapping have been described in approximately 80% of patients with moderate-to-severe asthma. 21 Oguzuglen and coworkers, in a study of 1680 patients with asthma, found that 3% of patients had radiographically evident bronchiectasis, and around 50% of patients with bronchiectasis had severe asthma. 1,2 Cylindrical bronchiectasis can be seen in 17-20% of patients with mild asthma, while the prevalence of bronchiectasis in severe asthmatics is more evident, though data on severe asthma population are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural changes are common in HRCT of patients with asthma, especially for those with more severe disease, as bronchial wall thickness and air trapping have been described in approximately 80% of patients with moderate-to-severe asthma. 21 Oguzuglen and coworkers, in a study of 1680 patients with asthma, found that 3% of patients had radiographically evident bronchiectasis, and around 50% of patients with bronchiectasis had severe asthma. 1,2 Cylindrical bronchiectasis can be seen in 17-20% of patients with mild asthma, while the prevalence of bronchiectasis in severe asthmatics is more evident, though data on severe asthma population are limited.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,20 In a study evaluating the prevalence of bronchiectasis in asthma according to oral steroid requirement, bronchiectasis was found in 20% in the steroid depended group and only 4% in the nonsteroid depended group. 21 Oguzuglen and coworkers, in a study of 1680 patients with asthma, found that 3% of patients had radiographically evident bronchiectasis, and around 50% of patients with bronchiectasis had severe asthma. 13 However, other causes of bronchiectasis were not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…21 In a case-control study matching patients with steroid-dependent asthma to those managed without regular oral corticosteroids, it was noted that bronchiectasis was much more common in the former group and the overall prevalence of otherwise unexplained bronchiectasis was 12% across both groups, rising to 20% in the steroid-dependent group. 22 …”
Section: Sectionmentioning
confidence: 99%
“…Several chronic respiratory diseases (usually those with an inflammatory profile) can trigger (or be associated with) bronchiectasis. Two of them in particular have attained special prominence in recent years due to their epidemiological impact: chronic obstructive pulmonary disease (COPD), including alpha-1 antitrypsin deficiency (α1-ATD) 2,3 and asthma 4 . However, the associations between COPD/asthma and bronchiectasis are not devoid of controversy, for various reasons.…”
Section: Introductionmentioning
confidence: 99%